Front Cover: Hydrogen Diffusion Guided Design of Pt‐Based Alloys for Inhibition of Butadiene Over‐Hydrogenation (ChemPhysChem 14/2019). Issue 14 (17th July 2019) - Hu, Chaoquan; Sun, Jiahan; Wang, Dongjie; Peng, Mi; Shao, Mingyuan; Zhu, Qingshan; Ma, Ding
Abstract : The Front Cover shows the inhibition of C=C bond hydrogenation by increasing the barrier for H atom diffusion to the site, on which the H atom shares two Pt atoms with the C=C bond. More information can be found in the Article by C. Hu et al. on page 1804 in Issue 14, 2019 (DOI: 10.1002/cphc.201900380 ).